Pengaruh Gaya Kepemimpinan Kepala Madrasah dan Pengawasan Kepala Kantor Kementerian Agama Kabupaten Pandeglang Terhadap Peningkatan Mutu Sarana dan Prasarana Pendidikan di MAN 2 Pandeglang dan MA Syekh Manshur - Maman Mansur; Shobri; Yus'aini (Formosa Journal of Social Sciences (FJSS), 2022)
An educational institution is said to have good quality education if it can meet all national education standards, one of which is the standard of facilities and infrastructure. The head of the madrasa is expected to be able to manage educational facilities and infrastructure well so that the educational facilities and infrastructure in the madrasa can be used optimally for the benefit of learning. There is also the role of the head of the office of the ministry of religion as the direct supervisor of the head of the madrasa who oversees the performance of the head of the madrasa. The formulation of the problem in this study are: 1) Is there any influence of the madrasa principal's leadership style on improving the quality of educational facilities and infrastructure? 2) Is there any effect of supervision of the head of the ministry of religion on improving the quality of educational facilities and infrastructure? 3) Is there any influence of the leadership style of the madrasa head and the supervision of the head of the ministry of religion on improving the quality of educational facilities and infrastructure? The objectives to be achieved from this research are as follows: 1) To find out whether or not there is an influence of the madrasa principal's leadership style on improving the quality of educational facilities and infrastructure. 2) To find out whether or not there is an influence of the supervision of the head of the ministry of religion on improving the quality of educational facilities and infrastructure. 3) To find out whether or not there is an influence of the leadership style of the madrasa head and the supervision of the head of the ministry of religion on improving the quality of educational facilities and infrastructure.